Global turn in art history and methodological constellations on artistic circulation. Perspectives, ideas, and operational concepts. - Iorio, Francesca (Eikón / Imago, 2024)
This article is situated within the context of exploring transnationality, circulation, and mobility as methodological devices/operational concepts in analyzing artistic artifacts, artists, and knowledge in motion. It delves into the interaction between art history and the global configuration of the contemporary age, reflecting on the application of methodological proposals from the global turn in the social sciences to the analysis of artistic mobility during the early modern period. Within this broader exploration, the article delves into the multifaceted nature of the genesis of reflections that have led to the emergence of global art history as a constellated phenomenon. It argues that the questioning of paradigms and the introduction of new terminology into the discipline cannot be solely attributed to art history itself. Instead, it emphasizes the need to examine the close association between this approach and broader movements of thought and historiography. At its core, the article highlights the crucial need for reevaluating language, lexicon, and research practices within historiographical movements. It advocates for the deconstruction of existing narratives and the creation of counter-narratives through a reconsideration of the terminology employed. This process fosters imaginative exploration bringing artistic analysis closer to current debates and ongoing reformulations of research practices.